2023
DOI: 10.1017/s1478951523001505
|View full text |Cite
|
Sign up to set email alerts
|

The roles and experiences of medical interpreters in palliative care: A narrative review

Claire Slusarz

Abstract: Objectives Skilled medical interpreters are essential to providing high-quality, culturally sensitive palliative care and addressing health-care disparities for patients with limited English proficiency (LEP). While the benefits of utilizing medical interpreters are well documented, interpreter roles and experiences in palliative care are unique and poorly defined. This narrative review examines the extant literature on medical interpreters in palliative care to define their unique roles and describe thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Providing accessible, culturally sensitive care is a priority for the palliative care community as a whole (National Consensus Project for Quality Palliative Care, 2018). To achieve this, including professional medical interpreters as integral members of interprofessional healthcare teams is imperative (Hsieh & Kramer, 2012;Latif et al, 2022b;Slusarz, 2023;Wu & Rawal, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing accessible, culturally sensitive care is a priority for the palliative care community as a whole (National Consensus Project for Quality Palliative Care, 2018). To achieve this, including professional medical interpreters as integral members of interprofessional healthcare teams is imperative (Hsieh & Kramer, 2012;Latif et al, 2022b;Slusarz, 2023;Wu & Rawal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although secondary traumatic stress (STS) and vicarious trauma have been investigated in medical interpreters caring for refugees and other populations, there is minimal quantitative data regarding the emotional impact of palliative care encounters on medical interpreters (Goldhirsch et al, 2022). Research has demonstrated medical interpreters play many roles when interpreting for palliative care patients such as interpreting language and meaning, acting as a cultural broker, and advocating for patients and families (Hordyk et al, 2017;Kirby et al, 2017;Latif et al, 2022a;Silva et al, 2020;Slusarz, 2023;Weaver et al, 2022). Interpreters have reported that navigating these complex and sometimes contradicting roles can present moral and ethical dilemmas that can cause emotional distress (Hordyk et al, 2017;Kirby et al, 2017;Norris et al, 2005;Rhodes et al, 2021;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%